Principles of bone and joint injuries and their healing - Nyary, Tamas; Scammell, Brigitte E. (Elsevier, 2018)
This article describes the mechanisms of fracture healing (direct and indirect), general fracture management, the influence of the surgeon on the biology and biomechanical environment of bone healing, the management of articular fractures, and disorders of bone union.